UMPSA Strategic Plan 2026–2030 (UMPSA30) to Drive the University’s Continued Excellence - Saharudin, Ramli (UMPSA, 2025)
PUTRAJAYA, 4 July 2025 – Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) continues to strengthen its position as a globally recognised technical higher education institution through the UMPSA Strategic Plan 2026–2030 (UMPSA30), which has been structured and is now in its final phase before its official launch later this year.